Giant Fronto-parietal Encephalocele: A rare case report - Dalal, Poonam; Rattan, KN; Gupta, Mohit; Rattan, Ananta (Indian Journal of Case Reports, 2015)
Although encephaloceles are common, but giant encephaloceles are rare with only few published short series and are mostly described in occipital location. Giant frontal encephaloceles are very rarely reported with only four published case reports in the world literature and giant encephalocele in fronto-parietal region has not been reported till date. Herein, we report a rare case of giant frontoparietal encephalocele in a six month old girl.